Severe malaria is associated with parasite binding to endothelial protein C receptor. - Turner, L; Lavstsen, T; Berger, S; Wang, C; Petersen, J; Avril, M; Brazier, A; Freeth, J; Jespersen, J; Nielsen, M; Magistrado, P; Lusingu, J; et al. (2013)
Sequestration of Plasmodium falciparum-infected erythrocytes in host blood vessels is a key triggering event in the pathogenesis of severe childhood malaria, which is responsible for about one million deaths every year. Sequestration is mediated by specific interactions between members of the P. falciparum erythrocyte membrane protein 1 (PfEMP1) family and receptors on the endothelial lining. Severe childhood malaria is associated with expression of specific PfEMP1 subtypes containing domain cassettes (DCs) 8 and 13 (ref. 3), but the endothelial receptor for parasites expressing these proteins was unknown. Here we identify endothelial protein C receptor (EPCR), which mediates the cytoprotective effects of activated protein C, as the endothelial receptor for DC8 and DC13 PfEMP1. We show that EPCR binding is mediated through the amino-terminal cysteine-rich interdomain region (CIDRα1) of DC8 and group A PfEMP1 subfamilies, and that CIDRα1 interferes with protein C binding to EPCR. This PfEMP1 adhesive property links P. falciparum cytoadhesion to a host receptor involved in anticoagulation and endothelial cytoprotective pathways, and has implications for understanding malaria pathology and the development of new malaria interventions.